Balance, basic anthropometrics and performance in young Alpine skiers; Longitudinal analysis of the associations during two competitive seasons - Lesnik, B.; Sekulic, D.; Supej, M.; Esco, M. R.; Zvan, M. (Journal of Human Kinetics, 2017)
Balance is hypothesized to be important in alpine skiing, while it is known that balance depends on anthropometric indices. The aim of this investigation was to explore the association between balance, anthropometrics and skiing-results over two competitive seasons among youth alpine-skiers. Eighty-one skiers (40 females) participated in this study. The participants were tested twice over two competitive seasons: when they were 12-13 years old (U14) and when they were 14-15 years old (U16). The variables consisted of anthropometrics (body height and body mass) and three balance indexes (medio-lateral-, anterio-posterior- and overall-stability-index). Additionally, skiing results in U14 and U16 were evaluated. The balance status did not change significantly over the observed period of time regardless of the significant changes in body mass and height. The relationships between balance and skiing results were higher in the U14 (Pearson`s r = 0.45-0.54) than in the U16 (Pearson`s r = 0.05-0.28). The relationships between anthropometrics and competitive results were generally stronger in girls (Pearson`s r = 0.39-0.88) than in boys (Pearson`s r = 0.26-0.58). After clustering athletes into three achievement groups on a basis of their competitive performance, discriminant canonical analysis showed that relationships between balance and skiing results decreased, while the relationships between anthropometrics and skiing results increased over the two observed seasons. This study highlighted the importance of balance in youth alpine skiing in the age range of 11-14 years.